Aspek Sosial dalam Novel 5 cm Karya Donny Dhirgantoro: Pendekatan Sosiologi Sastra - Ita Purnowowati (UHAMKA Graduate School Thesis Abstract Collection, 2016)
The study entitled "Social Aspects of the Novel 5 cm work Donny Dhirgantoro (Sociological Approaches to Literature)" is a description of a qualitative research approach to the sociology of literature. Issues addressed in this study are: (1) How does the social aspect which is described in the novel 5 cm written by Donny Dhirgantoro? (2) How does the social aspect in terms of the intrinsic structure of the novel 5 cm? (3) How does the social aspect of the novel 5 cm from the viewpoint of the author? The purpose of this study was to describe the intrinsic elements of novel 5 cm. The social aspect is contained in the novel 5 cm. The results of this study are expected to be useful for Indonesian Language and Literature Teachers, researchers themselves and society. This research method is qualitative description, whereas the research approach is sociological approach that emphasizes literary texts as an object of study. The data in this study is a word, phrase, clause, sentence, and discourse contained in the novel 5 cm. The object of this study is novel 5 cm of the issuer PT. Grasindo, Jakarta, 2005. Data collection methods used were of Library Studies. The instrument of this study is the researchers themselves to use qualitative data analysis tables refer to qualitative data analysis Emzir. The results of this study are: the intrinsic elements, there are four that are the focus, namely: the theme, characters, plot, and setting. The four elements are mutually reinforcing and together to build a narrative integrity of the novel 5 cm, the author describes the social aspect through the events that build the storyline. Way of thinking of the characters, the dialogue between characters, and the background of events, both physical and social background.